2009
DOI: 10.4161/auto.5.3.7784
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy facilitates the progression of ERα-positive breast cancer cells to antiestrogen resistance

Abstract: A major impediment to the successful treatment of estrogen receptor alpha (ERalpha)-positive breast cancer is the development of antiestrogen resistance. Tamoxifen, the most commonly used antiestrogen, exerts its pharmacological action by binding to ERalpha and blocking the growth-promoting action of estrogen-bound ERalpha in breast cancer cells. Tamoxifen treatment primarily induces cytostasis (growth arrest) and the surviving breast cancer cells commonly acquire tamoxifen resistance. Numerous clinically-rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
89
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 30 publications
1
89
0
Order By: Relevance
“…Recent studies have demonstrated that autophagy (also referred to as macroautophagy) is critical to the development of anti-estrogen resistance (130). This pro-survival role for autophagy in anti-estrogen-treated breast cancer cells is consistent with one function of the autophagosomes, which is to recycle metabolites from degraded cellular constituents to support a basal level of cell maintenance under starvation conditions and OS, thus rendering it essential for cellular viability.…”
Section: Role For Autophagy In Anti-estrogen Resistancementioning
confidence: 79%
“…Recent studies have demonstrated that autophagy (also referred to as macroautophagy) is critical to the development of anti-estrogen resistance (130). This pro-survival role for autophagy in anti-estrogen-treated breast cancer cells is consistent with one function of the autophagosomes, which is to recycle metabolites from degraded cellular constituents to support a basal level of cell maintenance under starvation conditions and OS, thus rendering it essential for cellular viability.…”
Section: Role For Autophagy In Anti-estrogen Resistancementioning
confidence: 79%
“…Autophagy is a key mechanism of cell survival in ER-positive breast cancer cells, resulting in the development of tamoxifen resistance (21). Also, antiestrogen resistance could be reduced by targeting autophagosome function, which is regulated by LC-3, Beclin-1, Atg-5, and Atg-12 (21)(22)(23), suggested that high Pin1 expression in tamoxifen-resistant MCF7 cells may enhance autophagy through increased expression of autophagy-related proteins, such as LC-3, to produce tamoxifen resistance. As expected, LC-3 levels were higher in tamoxifen-resistant MCF7 cells, and Pin1 overexpression produces the same expression patterns as tamoxifen-resistant cells, suggesting that Pin1 regulates tamoxifen resistance via enhanced LC-3 expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…41 Compromising autophagy by Beclin 1 inhibition or siRNA greatly increases the cytotoxicity of the antiestrogen 4-hydroxytamoxifen in breast cancer cells. 42 However, the opposite reaction of Beclin 1 to tumor therapy was also detected. In lung and breast cancer cells, inhibition of Beclin 1 results in radiation resistance, and overexpression of Beclin 1 potentiates the sensitivity of wild-type cancer cells to radiation.…”
Section: Patients and Materialsmentioning
confidence: 99%